Diagnostic value of IL-22, IL-23, and IL-17 for NK/T cell lymphoma: Diagnostic value of IL-22, IL-23, IL-17 for NKTCL - Qi, Yan; Liao, Bin; Chen, Jiawei; Liang, Chunling; Chen, Zesong; Xie, Baozhen (Cellular and Molecular Biology, 2023)
NK/T cell lymphoma (NKTCL) is a common blood cancer, and early diagnosis of this disease is crucial. This study is aimed to investigate the roles of IL-17, IL-22 as well as IL-23 for the diagnosis of NKTCL. Sixty-five patients with NKTCL were included and the blood samples were collected, and sixty healthy objectives served as the controls. Serums of the patients and controls were collected. The expression levels of IL-17, IL-22, and IL-23 were examined using enzyme-linked immunosorbent (ELISA) assay. The receiver operator characteristic (ROC) curve was drawn for determining the potential diagnostic value of these cytokines. The serum levels of IL-17 (156.0 ± 67.75 pg/mL), IL-22 (39.98 ± 23.88 pg/mL), and IL-23 (43.05 ± 25.69 pg/mL) were all markedly increased in NKTCL patients (P<0.001); ROC analysis showed the serum level of IL-17, IL-22, and IL-23 could serve as the potential diagnostic biomarker for NKTCL with high sensitivity and specificity. The AUC of IL-17 was 0.9487 (95% confidence interval (CI), 0.9052 to 0.9922). Area under the curve (AUC) of IL-22 was 0.7321 (95% CI, 0.6449 to 0.8192). The AUC of IL-23 was 0.7885 (95% CI, 0.7070 to 0.8699). Our data indicated that IL-17, IL-22, and IL-23 were all increased in NKTCL and may function as potential diagnostic biomarkers for NKTCL.